2021
DOI: 10.1002/pds.5258
|View full text |Cite
|
Sign up to set email alerts
|

New‐user and prevalent‐user designs and the definition of study time origin in pharmacoepidemiology: A review of reporting practices

Abstract: Background: Guidance reports for observational comparative effectiveness and drug safety research recommend implementing a new-user design whenever possible, since it reduces the risk of selection bias in exposure effect estimation compared to a prevalent-user design. The uptake of this guidance has not been studied extensively.Methods: We reviewed 89 observational effectiveness and safety cohort studies published in six pharmacoepidemiological journals in 2018 and 2019. We developed an extraction tool to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Previous studies have also highlighted the incomplete reporting and potential bias in the implementation of observational studies. Luijken et al found that 6% of the evaluated observational studies did not specify if new users or prevalent users were included, and in only half of the studies using new user design, time point of eligibility, treatment initiation, and start of follow-up were synchronized [ 44 ]. Due to these avoidable methodological pitfalls, the results of observational studies could be biased and mislead healthcare decisions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also highlighted the incomplete reporting and potential bias in the implementation of observational studies. Luijken et al found that 6% of the evaluated observational studies did not specify if new users or prevalent users were included, and in only half of the studies using new user design, time point of eligibility, treatment initiation, and start of follow-up were synchronized [ 44 ]. Due to these avoidable methodological pitfalls, the results of observational studies could be biased and mislead healthcare decisions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were defined as “users” or “nonusers” based on whether they had at least one dispensing of a lipid-lowering medication during the landmark period (within 90 days of discharge) [14]. Users were further classified as prevalent (continuing) or new users based on whether they were dispensed lipid-lowering medications within 90 days prior to stroke [15, 16]. Dispensing records were obtained from the PBS dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Time-related biases are typically introduced when baseline or follow-up–related time points differ between the study groups. Therefore, aligning the three time points—meeting eligibility, initiating treatment, and starting follow-up—is crucial to reduce these biases in a comparative effectiveness study [ 11 , 12 ]. One solution is to use a new-user, active-comparator design, that is, comparing new users of treatment of interest with new users of alternative therapy (ideally with the same indication) [ 1 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers may want to compare against non-users for their study purposes, or because of the absence of a proper active comparator. Indeed, of 89 studies on drug effectiveness or safety using RWD, 34% used a non-user comparator [ 12 ]. However, comparison with non-users poses a significant challenge in setting the time zero because non-users do not have a time point for starting treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation